Acalypha indica root extract increases post-hypoxic rat hippocampal tissue culture cell viability via phospholipase A2 inhibition (Faculty of Medicine Universitas Indonesia, 2013)
Background: Phospholipase A2 (PLA2) is involved in inflammation and cell death following stroke, and inhibition of its activity may promote neuroregeneration. This study aimed to observe the influence of Acalypha indica Linn root extract towards relative cell viability and PLA2 enzyme level in post-hypoxic hippocampal tissue culture. Methods: Experimental in vitro study using 24 primary neuronal cell cultures obtained from Sprague Dawley rat exposed to hypoxia with 5% O2 / 5% CO2 / N2 balanced gas for 24 hours. Post-hypoxia, Acalypha indica Linn root extract was added at doses of 10, 15, and 20 mg/mL to three treatment groups. No treatment was given to the control group. Each group consists of six samples. After 72 hours of incubation, relative cell viability was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) examination, and phospholipase A2 enzyme level was determined using ELISA. Results: PLA2 enzyme level of rat hippocampal tissue culture treated with Acalypha indica Linn root extract at 10, 15, and 20 mg/mL were significantly lower than that of control (5.55 ng/mL, 6.85 ng/mL, and 7.42 ng/mL vs 7.96 ng/mL, p < 0.05). Conclusion: Acalypha indica Linn root extract increases the relative cell viability and decreases the PLA2 enzyme level of post-hypoxic mouse hippocampal tissue with the optimal dose of the extract at 10 mg/mL.